WITHDRAWAL: Essential Oil Chemical Characterization and Antibacterial Activities of Lepidium sativum Seed - Gashaw Nigussie; Dinkayehu Desta; Sintayehu Ashenafi; Yemane Werede (Journal of Tropical Pharmacy and Chemistry, 2021)
Lepidium sativum plants are available abundantly in all part of Ethiopia and traditionally used for the treatment of various ailments. The work done on essential oil chemical characterization and biological activity of this plant are still insufficient reports in Ethiopia. Therefore the aim of the present study was to carry out essential oil chemical characterization and antibacterial activities of the seeds extracts and oils of L. sativum obtained from the local area Kersu Kebele, Goma Wereda, Jimma zone. The study was conducted by extraction of the seeds with organic solvents n-hexane, dichloromethane, ethyl acetate and methanol. The study performed on extraction of essential oil of the seed through hydrodistillation and investigation of phytochemical constituents of each solvent extract. The n-hexane extract (oil) and the essential oil of the seed extract were analyzed with GC-MS and 11 components were obtained from each types of oil. 7, 10, 13-hexadecatrienoic acid (64.42%) and Indol (63.78%) were the major components of n-hexane extracted and essential oil of the seeds respectively. Moreover both oils were held unsaturated fatty acid, saturated fatty acid and aromatic derivative compounds. The preliminary phytochemical test revealed the presence of alkaloids, flavonoids, glycosides, phenols, saponins, anthraqunnes, and tannins. Antibacterial activities of the essential oil were implemented by disc diffusion method against one Gram positive bacterium Stphylococus aureus and three Gram negative bacteria: E.coli, Proteus mirabilis and Klibsiella pneumoniae. The inhibition zones of the samples were compared with standard drug ceftriaxone. The essential oil showed antibacterial activities on all the tested bacteria.